IMPLEMENTASI ALGORITMA HAVERSINE PADA APLIKASI PENCARIAN LAYANAN KESEHATAN BERBASIS ANDROID - Tiwi, Heri Susan; Santa, Kristofel; Rorimpandey, Gladly C (LPPM Unbaja, 2024)
The development of information technology has changed people's life patterns by enabling easy access to information via smart devices such as smartphones. One of the pressing needs is easy access to information on nearby health services, especially in emergency situations or to get timely treatment. This research aims to develop an Android-based health service search application by utilizing the Haversine algorithm and Google Maps API. The Google Maps API was chosen because of its ability to provide accurate location data and various visualization features that help users navigate. The result of this research is a health service search application that utilizes the Haversine algorithm to calculate the distance between users and the nearest health facility to easily find health services that suit their needs based on the closest location. Application testing shows satisfactory results, with a high level of accuracy in determining the location of the nearest health facility. This application is expected to be an effective solution in making it easier for people to find the nearest health services quickly and efficiently via their smart devices.